2016
DOI: 10.1590/0103-8478cr20141795
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest quality and functional compounds in "dedo-de-moça" 'BRS Mari' pepper fruit at different stages of maturity

Abstract: The purpose of this study was to evaluate the physicochemical characteristics and functional properties of "dedo-de-moça" 'BRS Mari' pepper fruits at different maturity stages, and determine the ideal harvest stage for fresh consumption. The pepper plants were grown in the experimental field of Embrapa Hortaliças (Brasília, DF, Brazil) in 2012, and their fruits were evaluated at 20, 30, 40, 50, 60, 70, and 80 days after anthesis (DAA) RESUMO O objetivo deste trabalho foi avaliar as características físico-q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 13 publications
3
3
0
Order By: Relevance
“…3E). Using PVC and polyethylene terephthalate (PET), [12] observed that storage time, at temperature of 10°C ± 1°C, did not affect SS and TA contents and the SS/TA ratio of pepper, which corroborates with the data obtained in this research.…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…3E). Using PVC and polyethylene terephthalate (PET), [12] observed that storage time, at temperature of 10°C ± 1°C, did not affect SS and TA contents and the SS/TA ratio of pepper, which corroborates with the data obtained in this research.…”
Section: Methodssupporting
confidence: 89%
“…Studies with natural phenolic compounds, such as salicylic acid and plastic films, are important measures for preserving color and quality of the pepper [12], which justifies conducting studies in this area.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the luminosity and the hue angle showed a decrease along the stages of maturation, with the highest values observed in the green stage and the lowest values in the red stage (Table 3). These results coincide with those of Soethe et al (2016), who found a decrease in the values of luminosity and hue angle with the maturation of 'dedo-de-moça' peppers.…”
Section: /8supporting
confidence: 91%
“…Thus, during ripening, the color of the peppers is altered due to the degradation of chlorophyll and the synthesis of carotenoids, giving different shades of colors to the epidermis, being the main color used as an indicator of ripening the red color (Rêgo et al, 2011). In addition to color change, other parameters are altered during fruit ripening, affecting the dimensions, cell wall composition, synthesis of aromatic compounds, conversion of starches to sugars, and the ratio of sugars to acids, which provide texture, aroma, and flavor to the fruit (Pereira et al, 2014;Soethe et al, 2016;Villa-Rivera & Ochoa-Alejo, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation